Efficacy of Various Estrus Synchronization Protocols in Improving Conception Rate in Surti Goats - Parmar, Chirag P; Patel, Jagdish A; Manzarul Islam, Md; Dhami, Arjan J; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of the study was to compare the efficacy of three different estrus synchronization protocols for estrus induction/synchronization and conception rate in Surti does. Forty adult non-pregnant Surti goats were selected and equally divided based on serum progesterone levels into four groups (n=10 each), viz., Group-1: Intravaginal sponge protocol with natural service by intact buck after sponge removal, Group-II: Double PGF2α injection protocol (11 days apart) with natural service within 48 to 144 h after 2nd PG injection, and Group-III: Ovsynch protocol with natural service after 2nd GnRH injection, and Group-IV: was kept as untreated control. Goats having progesterone level ≤0.8 ng/mL and ≥1.4 ng/mL was kept in Group-I and III, and in Group-II, respectively. The estrus response was found 100% in the goats kept under each treatment group and 30% in control during study period of two months. Estrus induction intervals from last PGF2α injection were statistically similar in all treatment protocols. Significantly (p
Keywords: Conception rate, Double PG injection; Estrus synchonization; Ovsynch; Surti goats; Vaginal sponge